Phytochemical estimation and antioxidative potential Of thunbergia mysorensis (wight) t. Anders. Ex bedd in Uttarakhand, india - MANEESHA SINGH; GUNJAN KIMOTHI (International Journal of Pharma and Bio Sciences, 2018)
Free radicals and reactive oxygen species are well known inducers of molecular, cellular and tissue pathogenesis posing several threats to the human society. Antioxidants are compounds capable either to delay or inhibit to the oxidation processes which occur under the influence of atmospheric oxygen or reactive oxygen species. Antioxidants are involved in the defence mechanism of the organism against the pathologies associated with the attacks of free radicals. Many plants contain antioxidant compounds and these compounds protect cells against the damaging effects of reactive oxygen species (ROS) such as singlet oxygen, superoxide, peroxyl radicals, hydroxyl radicals and per-oxy nitrite which results in oxidative stress leading to cellular damage. Thunbergia mysorensis(Wight) T. Anders.exBedd (Acanthaceae family), is an extensive, glabrous climber with pendant branches and it is used to treat various diseases such as cough, jaundice, live disease, fever etc. Therefore, the present study comprises of collection of the plant material from Dehradun, Uttarakhand followed by ethanol extraction for qualitative and quantitative estimation of its phytoconstituents and antioxidant potential. The percentage yield of crude extract was 4.7% and dark green in colour. Phytochemical studies showed the presence of protein, alkaloid, amino acid, carbohydrate, flavonoids, tannin, phenolics. The phenol and flavonoid concentration of plant extract was 0.264μg/ml,0.259μg/ml respectively, and its reducing power activity is 0.311μg/ml. The IC50 value of the plant sample was 125μg/ml against the IC50 value of the standard (Ascorbic acid) was 237.5μg/ml. These finding suggested for the first time that Thunbergiamysorensis(Wight) T. Anders. ExBedd cultivation should be promoted as a medicinal plant as it is rich in phenolic and flavonoids compounds which are good sources of antioxidants. Thus in future, the plant extract could be used to control various diseases such as cough, jaundice, liver diseases, fever, arthritis etc. and the presence of phenols and flavonoids makes this plant as a source of good antioxidants.